Generates Warning Signals Based on Number Plate Recognition to Prevent Parking Violations - Sony Alfathani, Ahmad; Ar Roiyyaan, Rilwanu; Rinanda Saputri, Fahmy (International Journal of Science, Technology & Management, 2023)
Parking violations are very frequent around us, especially in urban areas, which greatly disturbs other road users so the government imposes strict sanctions on parking violations. To solve this problem, a surveillance system is needed to immediately alert drivers to move their vehicles to the correct parking space. In this paper, a monitoring system for parking violations has been developed that focuses on carrying out license plate recognition on cars and giving warnings to drivers to move their cars from the wrong parking location via voice media. The steps involved in license plate recognition are license plate detection, character segmentation, and character recognition by performing OCR (Optical Character Recognition). Furthermore, the license plate recognition results will be used as input for sound generation as a warning. In this paper, a GUI was also developed to help users run programs that have been developed. Finally, the experimental results show that a simple monitoring system to alert parking violations can be established.